EFEKTIVITAS PENGGUNAAN DAKON SATUAN PINTAR BERBASIS PBL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III - Huda Riyaya; Lingga Nico Pradana; Naniek Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine whether the Dakon Satuan Pintar media based on the Problem-Based Learning (PBL) model is effective in improving the mathematics learning outcomes of third-grade students. The subjects in this study were third-grade students at SDN 02 Nambangan Kidul. This study adopts a quantitative approach with a time series research type using a one-group pre-test post-test design. The sampling technique used was saturated sampling, with a total sample of 18 students. The research instruments consisted of pre-test and post-test in the third-grade mathematics subject. Data analysis results show a difference in the mathematics learning outcomes of third-grade students before and after learning using the Dakon Satuan Pintar media based on the PBL model, with the average score increasing from 53.89 to 82.22. Hypothesis testing indicates that the p-value < 0.01, specifically 0.00 < 0.01. Therefore, the study's findings demonstrate that the Dakon Satuan Pintar media based on the PBL model is effective in improving the mathematics learning outcomes of third-grade students.